Report of occurrence and endodontic management of three-rooted maxillary first and second premolars in the same individual - Kothandaraman Sathyanarayanan; Manali Ramakrishnan Srinivasan; Sundaresan Balagopal; Lingeswaran Poornima (Wolters Kluwer Medknow Publications, 2017)
Anatomical variations should be kept in mind in clinical and carefully looked for in radiographic evaluation during endodontic treatment of maxillary premolars. These teeth have highly variable root canal morphology. Although three separate roots in the maxillary first premolars have been reported, it is a rarity to find both the first and second premolars possessing three separate roots. This case report describes the diagnosis and endodontic management of maxillary first and second premolars with three canals and three separate roots. Access cavity refinements were required for stress-free entry to the complex anatomy.